Interventional Study on Reducing Stigma and Improving HIV/AIDS Awareness on Transmission among Housekeeping Workers in a Tertiary Care Hospital with Health Education (Indian Journal of Public Health Research & Development, 2024)
Background :Hospital housekeeping workers (HHW), also known as hospital janitorial staff, are individuals responsible for maintaining the cleanliness and hygiene of hospital facilities. This study focuses on the perceptions of HIV/AIDS among HHWs and their role in controlling its spread. The aims included assessing their knowledge of HIV/AIDS transmission, reducing stigma, and evaluating the impact of Information, Education, and Communication (IEC) on their awareness and perception.Methods :Conducted at a Chennai tertiary care hospital from December 2022 to January 2023, this interventional study involved 25 HHWs. The research utilised a structured questionnaire for socio-demographic details and HIV/AIDS-related questions, implementing pre- and post-tests after health education. Statistical analysis was performed using IBM SPSS Statistics v20.0. The chi-square test was used to arrive at a p-value to test the significance between pre- and post-intervention test results. A p-value of
Keywords: Marital status, Perception, HIV and AIDS prevention; hospital housekeeping workers; hiv stigma; HIV stigma in hospital; health education for destigamtisation; needle stick injuries in housekeeping staff; health education for hospital house keeping workers